The Satisfaction Level of Participants of the 5th Medical Students Scientific Olympiad in Iran in 2013 - Seiyed Davoud Nasrollahpour-Shirvani; Mostafa Javanian; Ali Shabestani-Monfared; Iman Jahanian (Kerman University of Medical Sciences, 2015)
Background & Objective: It is attempted to identify creative and talented individuals and to ensure the satisfaction of volunteers through creating a joyful atmosphere in scientific Olympiads The aim of the present study was to assess the level of satisfaction of candidates with the quality of the 5th National Medical Sciences Olympiad in Iran   Methods: This crosssectional study was conducted in the summer of 2013 The study population consisted of the candidates of the 5th National Medical Sciences Olympiad among the medical universities of Iran The subjects were selected through census method The data collection tool was a questionnaire designed by the researcher and its validity and reliability were confirmed Data were analyzed using SPSS software at a significance level of P < 0050   Results: Of the 222 studied candidates around the country 67 individuals (302%) studied Basic Sciences 52 (234%) Clinical Reasoning 67 (302%) Management of Health Systems and 36 (162%) Art in Medical Education The mean satisfaction level of candidates with the quality of this national Olympiad was 32 ± 11 and with the content and functionality of this Olympiad was 33 ± 12 There was a significant relationship between gender and satisfaction with the quality of the Olympiad (P = 0002) There was a significant relationship between age (P = 0 010 r = 0 131) semester (P = 0 019 r = 0122) and academic type (P = 0 019) and satisfaction with content and functionality of this Olympiad   Conclusion: Satisfaction with quality content and functionality of the 5th Olympiad was at a moderate level and thus requires improvements